Chemotherapy-induced peripheral neurotoxicity and complementary and alternative medicines: progress and perspective - Cheng, Xiao L.; Liu, Hong Q.; Wang, Qi; Huo, Jie G.; Wang, Xiao N.; Cao, Peng (Frontiers in Pharmacology, 2015)
Chemotherapy-induced peripheral neurotoxicity (CIPN) is a severe and dose-limiting side effect of antineoplastic drugs. It can cause sensory, motor and autonomic system dysfunction, and ultimately force patients to discontinue chemotherapy. Until now, little is understood about CIPN and no consistent standard of care is available. Since CIPN is a multifactorial disease, the clinical efficacy of single pharmacological drugs is disappointing, prompting patients to seek out alternative treatment options. Complementary and alternative medicines (CAMs), especially herbal medicines, are well known for their multifaceted implications and widely used in human health care. So far, several phytochemicals, plant extracts, and herbal formulas have been evaluated for their possible therapeutic potential in preventing onset and progression of CIPN in experimental models. Clinical acupuncture has also been shown to improve CIPN symptoms. In this review, we will give an outline of our current knowledge on the research advances of CIPN, the role of CAMs in alleviating CIPN and possible lacunae in research that needs to be addressed.